HEALTHY DIET ANALYSIS AS AN INDICATOR OF HEALTHY ISLAND ON BARRANG CADDI ISLAND - Rosmanely; Paluttur, Sukri; Saleh, Lalu Muhammad; Darmawansyah; Arifin, Muhammad Alwy; Syafar, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is an archipelago with 17,504 islands ranged from Sabang to Merauke and becomes one of the countries with the largest span of the archipelago in the world. The implementation of healthy island indicators has not been carried out yet because it still follows the Healthy Regency/City administration system in Indonesia. Okinawa island in Japan which is known as the world’s healthiest island has some indicators such as a healthy diet, social condition, and healthy diet consumption. This study is descriptive quantitative. The population of the study was 351 households living on the Barang Caddi island in Makassar, South Sulawesi Province. While the sample amounted to 153 persons. The data were collected using a questionnaire and analyzed in SPSS version 20. The chi-square test result showed no association was pronounced between the healthy diet and the healthy island (p=0.297). The majority of respondents claimed that the healthy diet for the island community was relatively low because they believed that high dietary intake is balanced with high activity levels. The food consumption of island community was also relatively simple as they rarely consume junk food or any type of fast food and rather process their own food either seafood or harvested food from their own yard such as Moringa oleifer leaves. It is recommended to the government of South Sulawesi and especially to agencies that deal with the island communities, especially remote islands that have difficult access, need to do a more comprehensive study, assessment, and application of appropriate indicators used for healthy islands in South Sulawesi.